Proceedings of the 1st International and Interdisciplinary Conference on Digital Environments for Education, Arts and Heritage EARTH 2018 - Luigini, Alessandro (Advances in Intelligent Systems and Computing, 2019)
This book gathers peer-reviewed papers presented at the 1st International and Interdisciplinary Conference on Digital Environments for Education, Arts and Heritage (EARTH2018), held in Brixen, Italy in July 2018. The papers focus on interdisciplinary and multi-disciplinary research concerning cutting-edge cultural heritage informatics and engineering; the use of technology for the representation, preservation and communication of cultural heritage knowledge; as well as heritage education in digital environments; innovative experiments in the field of digital representation; and methodological reflections on the use of IT tools in various educational contexts. The scope of the papers ranges from theoretical research to applications, including education, in several fields of science, technology and art. EARTH 2018 addressed a variety of topics and subtopics, including digital representation technologies, virtual museums and virtual exhibitions, virtual and augmented reality, digital heritage and digital arts, art and heritage education, teaching and technologies for museums, VR and AR technologies in schools, education through digital media, psychology of perception and attention, psychology of arts and communication, as well as serious games and gamification. As such the book provides architects, engineers, computer scientists, social scientists and designers interested in computer applications and cultural heritage with an overview of the latest advances in the field, particularly in the context of science, arts and education.